Endogenous insulin secretion even at a very low level contributes to the stability of blood glucose control in fulminant type 1 diabetes - Shibasaki, Saeko (Blackwell Publishing Ltd, 2010)
Fulminant type 1 diabetes is characterized by almost complete β‐cell destruction, resulting in scarce insulin secretion. In the present study, we aimed to clarify clinical features related to serum C‐peptide levels measured by a high sensitivity method, chemiluminescent enzyme immunoassay, in 12 patients with fulminant type 1 diabetes. Serum C‐peptide was detected (0.007–0.10 nmol/L) in four patients and was not detected in eight patients. A negative correlation was observed between serum C‐peptide levels and daily dosages of insulin (P < 0.01). The patients with detectable C‐peptide showed a significantly lower M‐value than those without (P = 0.01). In conclusion, our present results suggest that even very low levels of endogenous insulin secreting capacity can improve daily dosages of insulin and stabilize blood glucose levels. (J Diabetes Invest, doi: 10.1111/j.2040‐1124.2010.0059.x, 2010)